Bases de Schiff e aplicações biológicas utilizando a ferramenta de Docking molecular para atividade Antileishmaniose - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Leishmaniasis, a complex and pressing challenge in tropical regions, with a focus on the Northeast region of Brazil, emerges as a public health, economic, and political problem. The inadequacy of existing treatments, marked by their toxicity, high costs, and the emergence of resistance, accentuates the urgency to seek effective and accessible therapeutic alternatives. In this scenario, Schiff bases emerge as a promising line of research in the fight against leishmaniasis. These compounds, with their diverse biological activities, including antitumor, antimicrobial, analgesic, and anti-inflammatory properties, offer a range of possibilities for therapeutic innovations. The variety and versatility of these compounds reinforce their importance in the development of new formulas, with the potential to treat leishmaniasis and other diseases. The combination of natural and synthetic inhibitors appears as a viable strategy that could mitigate the limitations of conventional treatments, avoiding antimicrobial resistance and driving therapeutic innovation. The results of this study, obtained through the analysis of a library of 39 Schiff base compounds using computational modeling, highlight the feasibility of this approach. Compounds such as 3-Quinolinamine, 1,3-Bis[(E)-(2-Amino-4-Ethyl-5- Hydroxy-Phenyl)Methyleneamino]Urea, and Naphtaldehyde disulfide Schiff base showed significant affinity with the trypanothione reductase of Leishmania infantum compared to commercial inhibitors, suggesting their possible effectiveness against leishmaniasis. Thus, this study contributes to advancing knowledge and encourages future research in this field, offering promising perspectives for tackling leishmaniasis.
Schiff Bases and biological applications using molecular Docking as a tool for Anti-Leishmaniasis activity
Keywords: Bases de Schiff; Leishmaniose; Atividades biológicas; Atividade antileishmania; Schiff's bases; Leishmaniasis; Biological activities; Antileishmanial activity; CIENCIAS EXATAS E DA TERRA::QUIMICA